Long-term functional mobility and gait-related outcomes after single-event multilevel surgery in ambulatory children with cerebral palsy: A systematic review - Sufandi Fahmi; Tri Wahyu Martanto; Dwikora Novembri Utomo; Arif Zulkarnain; Hizbillah Yazid (Universitas Udayana dan Diaspora Taipei Medical University, 2026)
Background: Single-event multilevel surgery (SEMLS) is widely used to manage multilevel lower-limb deformities and gait impairment in ambulatory children with cerebral palsy. However, the long-term relationship between gait correction, functional mobility, biomechanical outcomes, and the need for additional surgery remains incompletely defined. This systematic review evaluated long-term functional mobility and gait-related outcomes after SEMLS or related multilevel surgical procedures in ambulatory children and adolescents with cerebral palsy. Methods: A systematic literature search was conducted in PubMed and Scopus. Long-term follow-up was defined as postoperative follow-up exceeding 12 months. Eligible studies included original clinical studies evaluating SEMLS, multilevel gait improvement surgery, or procedure-specific interventions performed as part of a multilevel surgical approach in ambulatory individuals with cerebral palsy. Functional mobility outcomes included Functional Mobility Scale (FMS), Gillette Functional Assessment Questionnaire Walking Scale (FAQWS), Gross Motor Function Classification System (GMFCS), assistive device use, and wheelchair use. Gait-related outcomes included global gait indices, three-dimensional gait analysis, spatiotemporal parameters, kinematic and kinetic variables, and biomechanical measures. Methodological quality was assessed using MINORS, and findings were synthesized narratively. Results: Of 480 identified records, 10 studies met the inclusion criteria. Functional mobility outcomes showed maintenance or improvement of ambulatory ability after SEMLS, although outcomes varied according to baseline GMFCS level and walking distance. Patients with GMFCS levels I–II generally demonstrated more favorable household and community mobility than those with GMFCS level III. Global gait indices, including GPS, GDI, EVGS, and GGI, generally improved after SEMLS. However, residual abnormalities such as pelvic tilt, swing-phase knee motion, postoperative back-kneeing, and recurrent crouch gait were also reported. Several long-term cohorts reported additional orthopedic surgery because of recurrence, residual deformity, or newly developed biomechanical problems. Conclusion: SEMLS was associated with favorable long-term functional mobility and gait-related outcomes in ambulatory cerebral palsy. However, postoperative outcomes remained heterogeneous across functional level, gait domain, surgical composition, and follow-up duration.